Metabolic Biomarkers of Mediterranean Diet in Pregnant Women. (7th June 2021) - Dai, Jin; Chen, Liwei; Fei, Zhe; Liu, Xinyue; Zhu, Yeyi; Hinkle, Stefanie N; Wu, Jing; Lu, Ruijin; Rahman, Mohammad L; Chen, Zhen; Song, Yiqing; Zhang, Cuilin
Abstract: Objectives: Using an untargeted approach to identify plasma metabolomics signature of the Mediterranean diet, a healthful dietary pattern related to both maternal and fetal outcomes, in pregnancy. Methods: This study included 193 pregnant women from the NICHD Fetal Growth Studies-Singletons (FGS) cohort who had habitual dietary intake in the past three months measured at 8–13 gestational weeks (GW) by the semi-quantified food frequency questionnaire. Fasting plasma metabolomics profiles at 15–26 GW were measured by the high-throughput liquid chromatography quadrupole time of-flight mass spectrometry (LC-QTOF MS/MS). Metabolites were re-scaled to a median of 1 for each batch and log transformed. Alternate Mediterranean Diet (aMED) score was calculated by eight food and nutrient components (i.e., fruits, vegetables, whole grains, nuts, fish, legumes, red and processed meats, and monounsaturated-to-saturated fat ratio), with a higher score indicating a better adherence. Prospective associations of aMED score in peri-conception and early pregnancy with individual metabolites at 15–26 GW were estimated using the linear regression adjusting for potential confounders and multiple testing. LASSO (Least Absolute Shrinkage and Selection Operator) regression with 10-fold cross-validation was performed to select metabolites that were jointly associated with high aMED score (defined as the top tertile). All statistical analyses were weighted to represent the entire FGS cohort. Results: A total of 460 known metabolites were profiled and annotated. Six metabolites were selected as the biomarkers of high aMED score by the LASSO regression (i.e., with no-zero coefficients). Among them, glutamic acid and 3-hydroxybutyric acid were negatively whereas PC (40:7), CE (20:5), TG (49:1), and TG (58:4) were positively associated with aMED score. The six biomarkers were also confirmed by the linear regression with false discovery rates < 0.1. Conclusions: Our study is the first one conducted in pregnant women using the untargeted metabolomics approach and we newly identified several biomarkers of Mediterranean diet in pregnant women. Results from this study warrant the replication by future studies. Funding Sources: The work was supported by the intramural research program of the NICHD and the internal fund from UCLA.